Structural and photoconductivity properties of silicon carbon thin films. Issue 11 (30th September 2014) - Coscia, U.; Ambrosone, G.; Basa, D. K.; Rigato, V.; Binetti, S.; Pizzini, Sergio; Kissinger, Gudrun
Abstract Nanostructured films composed of silicon crystallites dispersed in an hydrogenated amorphous silicon carbon matrix have been deposited by plasma enhanced chemical vapour deposition from silane‐methane mixtures diluted in hydrogen by varying the rf power. Compositional, structural, optical and photoconductivity properties of the films have been investigated. The increase in rf power in the 40‐80 W range enhances the incorporation of carbon and hydrogen in the amorphous matrix and decreases the volume fraction and size of the silicon crystallites leading to an enlargement of the optical band gap from 2.07 to 2.20 eV. Steady state photoconductivity measurements, performed under monochromatic radiations in the visible range, have demonstrated the occurrence of monomolecular recombination kinetics in the samples under illumination and that the mobility‐lifetime product of the free electrons as a function of the optical gap decreases from 1.9 × 10–7 to 2.5 × 10–9 cm2V–1 as in the case of device quality films deposited by silane‐methane mixtures diluted in hydrogen. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)